Clinical and symptomatological particularities in pediatric patients diagnosed with chronic hypertrophic rhinitis - Furculița, Daniel; Maniuc, Mihail; Danilov, Lucia; Ababii , Polina (The Ukrainian Scientific Medical Youth Journal, 2025)
Chronic hypertrophic rhinitis (CHR) is a common condition in pediatric ENT practice, significantly affecting children's quality of life through persistent nasal obstruction, respiratory disturbances, and associated symptoms. Despite its high prevalence, data on the symptomatological characteristics and effectiveness of surgical interventions in the pediatric population remain limited. The aim of the study was to analyze the clinical and symptomatological particularities of CHR in pediatric patients and to compare the effectiveness of two surgical treatment methods: bipolar forceps cauterization and diode laser surgery. The study included 128 patients aged between 7 and 18 years, diagnosed with CHR and divided into two equal therapeutic groups. Data were collected through clinical examinations, symptom questionnaires, paraclinical assessments, and imaging investigations. Symptom frequency, history of ENT interventions, and postoperative evolution were analyzed comparatively between the two groups. Nasal obstruction was present in 100% of patients, followed by anterior rhinorrhea (73.43%), oral breathing (65.6%), and snoring (59.3%). Adenoidectomy was the most frequently reported previous ENT intervention (39%). Both surgical methods led to symptom improvement, but diode laser surgery demonstrated a superior profile through faster reduction of nasal congestion, more favorable postoperative evolution, and a lower rate of complications. Chronic hypertrophic rhinitis presents a complex and variable symptomatology in children, requiring early diagnosis and personalized interventions. Diode laser surgery proved to be an effective and safe alternative compared to bipolar cauterization, supporting its extended use in pediatric ENT practice.